Pemanfaatan Teknologi Digital sebagai Penguat Modal Sosial-Budaya dalam Pendidikan Karakter Siswa Pedesaan - rizky12 nurwahid; Ikna Awaliyani (Jurnal Pendidikan Teknologi Informasi (J-Diteksi), 2026)
This research examines how digital technology can help strengthen social and cultural capital in the character education of students living in rural areas. Currently, technology is widely used in schools, but its use is still limited to communication and assignment submission. However, technology can be utilized more effectively to support local cultural values ​​and strengthen relationships between teachers, parents, and the community. Furthermore, villages possess strong social and cultural capital, such as the practice of mutual cooperation (gotong royong), a sense of togetherness, and local traditions and values ​​that are still practiced daily. These values ​​form the foundation for children's character education. A literature review of various studies found that technology can be a bridge to introduce and preserve local culture, for example through the creation of cultural videos, documentation of traditions, or other digital media. When local culture is packaged in digital form, students become more engaged and more easily understand the character values ​​being taught. The results of this study indicate that character education in rural areas will be stronger if technology is combined with existing social and cultural capital. Thus, technology is not simply a modern tool, but can be a new way to maintain cultural identity and shape students' character, keeping it relevant to current developments.